Impact of variable seawater conductivity on ocean wave-induced electromagnetic fields simulated with finite difference method - Ge, Jiaqi; Li, Yuguo (Frontiers in Earth Science, 2023)
Electric fields generated by the motion of ocean waves through the Earth’s ambient geomagnetic fields and the induced secondary magnetic fields can be observed at the seafloor, at the sea-surface and even in the air. Most of current studies on ocean wave-induced electromagnetic fields assume that seawater conductivity is constant, and ocean waves are treated as regular waves with a fixed amplitude and frequency. However, these assumptions are inconsistent with actual ocean conditions. In this paper, we present a finite difference algorithm for modeling the ocean wave-induced electromagnetic fields with variable seawater conductivity. We investigate impacts of variable seawater conductivity on the electromagnetic fields induced by the wind waves and swell as well as mixed waves, which are treated as the superposition of a number of regular waves with different frequencies and amplitudes, and analyze the characteristics of the induced electromagnetic fields.